2008
DOI: 10.1002/cbic.200700761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Fluorescein‐ and Biotin‐Labeled Molecular Probes for the Chemokine Receptor CXCR4

Abstract: The design, synthesis, and bioevaluation of fluorescence- and biotin-labeled CXCR4 antagonists are described. The modification of D-Lys8 at an epsilon-amino group in the peptide antagonist Ac-TZ14011 derived from polyphemusin II had no significant influence on the potent binding of the peptide to the CXCR4 receptor. The application of the labeled peptides in flow cytometry and confocal microscopy studies demonstrated the selectivity of their binding to the CXCR4 receptor, but not to CXCR7, which was recently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 45 publications
3
61
0
Order By: Relevance
“…In the model shown in Figure 1 the luminescent Ir III label does not appear to interfere with receptor binding, as the conjugation site in the peptide (d-Lys8) is distant from the pharmacophore, which consists of peptide residues 2, 3, 5 and 14. [10,11] Moreover, attachment of one or two additional Ac-TZ14011 moieties to the Ir III complex via a b-alanine spacer also does not appear to hinder the binding (Figure 1). …”
Section: Designmentioning
confidence: 92%
See 1 more Smart Citation
“…In the model shown in Figure 1 the luminescent Ir III label does not appear to interfere with receptor binding, as the conjugation site in the peptide (d-Lys8) is distant from the pharmacophore, which consists of peptide residues 2, 3, 5 and 14. [10,11] Moreover, attachment of one or two additional Ac-TZ14011 moieties to the Ir III complex via a b-alanine spacer also does not appear to hinder the binding (Figure 1). …”
Section: Designmentioning
confidence: 92%
“…[8,9] For CXCR4 targeting several peptidic probes have been reported, including the cyclic Ac-TZ14011 peptide, and also a chelate-based fluorescent probe. [10][11][12][13][14][15][16] Transition-metal complexes based on, for example, iridium-(III), rhenium(I) and ruthenium(II) are attaining significant interest for application in imaging. [17][18][19][20][21][22][23][24][25][26][27][28] These phosphorescent metal complexes often posses better photophysical properties than organic fluorophores, such as long luminescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous work with different T140 analogues (20) and the recent findings that the small molecule FC131 does not bind to CXCR7 (21) and does not induce arrestin recruitment to CXCR7 5 indicate that CXCR4 inhibitors do not inherently also bind CXCR7 and that receptor selectivity can be achieved. To our knowledge, synthetic chemokine receptor ligands that exert opposite effects on two different receptors are still unreported.…”
Section: Discussionmentioning
confidence: 99%
“…[8] There have been a few reports of optical imaging probes designed to target CXCR4; most involved fluorescently tagged peptides with high binding affinities. [9][10][11] In 2007, Archibald et al reported a small molecule with structural similarities to AMD3100 that also contained a fluorescent rhodamine attachment. [12] Whilst the uncomplexed compound did not inhibit the binding of CXCR4-specific monoclonal antibodies, the corresponding copper complex was shown to have more favourable binding properties.…”
Section: Introductionmentioning
confidence: 99%